2012
DOI: 10.1016/j.ajo.2011.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Complications in the Tube Versus Trabeculectomy (TVT) Study During Five Years of Follow-up

Abstract: Purpose To describe postoperative complications encountered in the Tube Versus Trabeculectomy (TVT) Study during 5 years of follow-up. Design Multicenter randomized clinical trial. Methods Settings Seventeen clinical centers. Study Population Patients 18 to 85 years of age who had previous trabeculectomy and/or cataract extraction with intraocular lens implantation and uncontrolled glaucoma with intraocular pressure (IOP) ≥18 mm Hg and ≤40 mm Hg on maximum tolerated medical therapy. Interventions Tube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
543
19
25

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 718 publications
(612 citation statements)
references
References 33 publications
25
543
19
25
Order By: Relevance
“…Recent studies have demonstrated good short‐term results with early postoperative complication rates even lower than after trabeculectomy (Gedde et al. 2012a,b). …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated good short‐term results with early postoperative complication rates even lower than after trabeculectomy (Gedde et al. 2012a,b). …”
Section: Introductionmentioning
confidence: 99%
“…Reported percentages vary from 2.0%, 5.0% and 8.3% to 8.5% (Gedde et al. 2012a,b; Ng et al. 2015; Trubnik et al.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing the number of tube exposures from our donor sclera cohort to the exposure rates reported in other studies using other patch graft materials, we observed a substantially lower rate (Gedde et al. 2012a,b; Trubnik et al. 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corneal decompensation following GDI surgery has been reported to be in the range 5-27%. 7,14,15 Corneal decompensation was a frequent occurrence in the study of sequential tube shunts by Burgoyne et al 2 In their study, 10 of 22 patients (45.5%) experienced new onset bullous keratopathy or had worsening of pre-existing pseudophakic keratopathy. One study, comparing GDI bleb revision with an additional GDI procedure after failed GDI surgery found corneal edema to be a common complication, especially in the additional tube group.…”
Section: Discussionmentioning
confidence: 99%